2015
DOI: 10.4103/0972-6748.160932
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive rehabilitation of attention and memory in depression

Abstract: Background:Cognitive deficits are an important component of depression and may remain impaired after recovery from depression.Objectives:To evaluate the efficacy of cognitive rehabilitation in depression on cognitive dysfunction in the area of attention and memory.Materials and Methods:The study was hospital based pre- and post-intervention with follow-up assessment design. Selection of the depressive patients was by purposive sampling. The sample size consists of 30 intervention depressive patients included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…[25][26][27] Additionally, the existing literature has also shown that psychological interventions can effectively improve anxiety related to PCC and address associated mental health concerns. 28 The results of our study support these findings as we identified a strong correlation between anxiety and well-being in PCC. Enhancing well-being is not only vital for an individual's health but may also help improve work productivity and reduce functional impairments, which are prevalent challenges faced by people with PCC.…”
Section: Key Findingssupporting
confidence: 86%
“…[25][26][27] Additionally, the existing literature has also shown that psychological interventions can effectively improve anxiety related to PCC and address associated mental health concerns. 28 The results of our study support these findings as we identified a strong correlation between anxiety and well-being in PCC. Enhancing well-being is not only vital for an individual's health but may also help improve work productivity and reduce functional impairments, which are prevalent challenges faced by people with PCC.…”
Section: Key Findingssupporting
confidence: 86%
“…It is also possible that older adults with depressive symptoms have limited processing efficiency due to ruminative thinking, which can preoccupy attentional resources (Eysenck et al ., ). Taken together, these findings suggest that interventions designed to improve attentional function, for example, through the use of “cognitive‐enhancing” drugs such as modafinil (Husain and Mehta, ) and cognitive rehabilitation (Priyamvada et al ., ), may help mitigate risk for chronic depressive symptoms in cognitively normal older men and women.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of cognitive training studies have been conducted with individuals having schizophrenia-spectrum disorders (Wykes et al, 2011), but there have been several recent studies of cognitive interventions for individuals with mood disorders (see meta-analysis by Motter et al, 2016). Most of the interventions studied in participants with mood disorders have been computerized (e.g., Bowie et al, 2013); some have been compensatory strategy-based (e.g., Priyamvada et al, 2015; Venza et al, 2016; Deckersbach et al, 2010), but there have been few controlled studies of compensatory strategy-based interventions, and no known trials of purely compensatory strategy-based interventions combined with employment interventions.…”
Section: Introductionmentioning
confidence: 99%